2019
DOI: 10.1164/rccm.201804-0646oc
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophage Apoptosis–associated Bacterial Killing Helps Prevent Murine Pneumonia

Abstract: This is a repository copy of Alveolar macrophage apoptosis-associated bacterial killing helps prevent murine pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 53 publications
(66 reference statements)
4
47
0
Order By: Relevance
“…This hypothesis‐testing study was based on evidence suggesting that N‐BPs may have similar effects on both alveolar macrophages and osteoclasts, cells that share the same lineage, and thus may influence the pathogenesis of pneumonia characterized by lung parenchyma inflammation. Alveolar macrophages play an important antibacterial role in defending against pneumonia by early phagocytosis of pathogens and subsequent induction of apoptosis to minimize inflammation . A clinical study showed that N‐BPs reduced macrophage lineage cells through the reduction of mcl‐1 expressions in both macrophages and osteoclasts, which might subsequently reduce inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis‐testing study was based on evidence suggesting that N‐BPs may have similar effects on both alveolar macrophages and osteoclasts, cells that share the same lineage, and thus may influence the pathogenesis of pneumonia characterized by lung parenchyma inflammation. Alveolar macrophages play an important antibacterial role in defending against pneumonia by early phagocytosis of pathogens and subsequent induction of apoptosis to minimize inflammation . A clinical study showed that N‐BPs reduced macrophage lineage cells through the reduction of mcl‐1 expressions in both macrophages and osteoclasts, which might subsequently reduce inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that differential expression of key pattern recognition receptors such as CD209b might endow female macrophages with an enhanced ability to deal with bacterial infection. To test this idea, we examined the acute peritonitis caused by the gram-positive bacterium Streptococcus pneumoniae (Figure 7a), a localised model of infection in which resident macrophages, and in particular CD209b, are indispensable for protective immunity 49, 50 whereas recruitment of neutrophils is not required 49 and hence avoids any confounding effects of systemic sex-dependent effects on innate immune responses that have been reported previously 51 . As CD209b is expressed exclusively by CD102 + macrophages in the peritoneal cavity ( Supplementary Figure 6 ), this model allowed us to directly assess the importance of differential CD209b expression by CD102 + macrophages in bacterial elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Across pneumococcal strains, those that more rapidly induce necroptosis tend to be more virulent in the lung (27), suggesting this mode of cell death to be a maladaptive pathway during pneumococcal pneumonia. In contrast, macrophage cell death by apoptosis appears to be a healthy response to pneumococcal infcetion, since specifically preventing macrophage apoptosis results in more severe lung infections (46). Pneumococcusinduced macrophage death is a complicated but important contributor to pneumonia outcomes.…”
Section: Discussionmentioning
confidence: 99%